Biomedical and biological applications of quantum dots. (2nd April 2016) - Abbasi, Elham; Kafshdooz, Tayebeh; Bakhtiary, Mohsen; Nikzamir, Nasrin; Nikzamir, Nasim; Nikzamir, Mohammad; Mohammadian, Mozhdeh; Akbarzadeh, Abolfazl
Abstract : Quantum dots (QDs) as colloidal nanocrystalline semiconductors have exceptional photophysical properties, due to their quantum confinement effects. Depending on their sizes and chemical compositions, QDs emit different wavelengths over a broad range of the light spectrum, from visible to infrared. QDs are typically extensively used for optical applications due to their high extinction coefficient. This article reviews biomedical applications of QDs, especially the application of QDs in cell targeting, delivery, diagnostics, cancer therapy, and imaging for cancer research.